KONSEP PENGEMBANGAN METODE DAKWAH MODERN - Fitria Akmal; Anhar Fazri (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2017)
This article discusses about da'wah in society in modern era which is currently experiencing problems. Development of da'wah method must also follow the current era even more with the way of utilization of communication technology into a benchmark development. In the past and present of course also differ especially the method of lecture and education of Islam directly by the Ulama, Ustad, Tengku and other religious experts of course very often we meet. However, at this time of increasingly advanced information systems would facilitate the people from all walks of life to get information anytime and anywhere. That way, all circles, especially Muslim scholars must also be able to master the information technology that is growing today such as mobile phones, emails, twitter, and other media that must be mastered as soon as possible to contain and educate Muslims better. The issue of aqidah, morals, materialistic becomes an urgent matter handled today let alone the issue of teenagers when viewed on the side of morals that increasingly become unfavorable, which they should become the next generation of nation, but they are now far from the word worthy to be said leader in the feature. By doing the development of da'wah method, of course also will give stimulus in all things to all society.